Biocompatibility of highly purified bovine milk-derived extracellular vesicles - Somiya, Masaharu (J Extracell Vesicles, 2018)
Extracellular vesicles (EVs) deliver biologically active cargos from donor cells to recipient cells for intercellular communication. Since the existence of RNA cargo was discovered, EVs have been considered to be useful drug-delivery systems. Specifically, EVs from bovine milk (mEV) are one of the most promising platforms, since bovine milk is a scalable source of EVs for mass production. However, it is still difficult to isolate pure EVs from bovine milk owing to the complexity of raw materials. Furthermore, the biocompatibility and immunotoxicity of mEVs are still unclear. In this study, we developed a new method for isolating bovine milk-derived EVs by employing acid treatment and ultracentrifugation. Isolated mEVs are spherical in shape, measure 120 nm in diameter and contain typical EV marker proteins, such as tetraspanins. Compared with the previously reported method, our method can isolate purer mEVs. When mEVs are contacted with the mouse macrophage cell line Raw264.7, mEVs are readily taken up by the cells without a cytotoxic effect, suggesting that mEVs can deliver the cargo molecules into cells. While systemic administration of mEVs into mice resulted in the absence of systemic toxicity, certain types of cytokines were slightly induced. No anaphylaxis effect was observed after serial administration of mEVs in mice. Thus, mEVs isolated using our method are well tolerated in vivo and may be useful for the drug-delivery application.